(untitled) (International Journal of Environmental Sciences, 2025)
This study presents the seismic qualification of an Exhaust Gas Silencer (EGS) installed in the Emergency Diesel Generator (EDG) system of a nuclear power plant. Using Finite Element Analysis (FEA) with ANSYS 12.1, the structural performance of the EGS was assessed under normal, upset (½ Safe Shutdown Earthquake), and faulted (Safe Shutdown Earthquake) conditions, in accordance with KEPIC MN Class 3 and ASME Section III standards. Modal analysis confirmed a fundamental natural frequency of 69.13 Hz, exceeding the 33 Hz threshold, thereby validating the use of equivalent static seismic analysis. Locations of analysis which were critical, including saddle supports, head-to-shell junctions and reinforced areas, proved that the maximum combined membrane and bending stresses did not exceed those defined by code. The maximum stress of 240.62 MPa was observed at the reinforced angle, which remained below the permissible stress of 243.12 MPa during faulted seismic loading. These findings justify the structural integrity and seismic resilience of the EGS.By maintaining emission control during seismic events, the qualified EGS ensures safe dispersal of exhaust gases, preventing uncontrolled environmental release and supporting sustainability in nuclear operations.The study also establishes a replicable and code-compliant methodology for qualifying auxiliary components in nuclear systems subjected to seismic loading.